KAIDAH PENAMAAN LEKSEM BENDA-BENDA KECIL (ISM TAṢGĪR) DALAM KAMUS AL-MUNAWWIR ARAB-INDONESIA (ANALISIS MORFOSEMANTIK) - Muhammad Yunus Anis, Arifuddin (CMES (Center of Middle Eastern Studies), 2020)
This article will generally examine the naming convention of small objects lexemes (ism tagīr) in the Al-Munawwir Arabic-Indonesian dictionary. The approach used in this study is a linguistic approach, especially closely related to morphosemantics. In this case, the morphosemantic study involves the study of the structure and meaning of the lexeme in relation to small objects or what is commonly referred to in Arabic as ism taṣgīr. The research method consists of three important stages, such as: (1) the data collection and analysis using the observation method of linguistic units in the form of "words" in the al-Munawwir dictionary, (2) the data analysis used distributional methods in the form of techniques for direct elements and contrasting techniques, and (3) reports on results related to the rules for naming small objects in Arabic. The results of this study are expected to provide new insights on the relationship between morphological word formation in Arabic and naming rules in Semantic studies.